2016
DOI: 10.1136/bcr-2016-216503
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral internuclear ophthalmoplegia, strabismus and transient torsional nystagmus in focal pontine infarction

Abstract: Vertebrobasilar stroke carries a high mortality rate and can have symptom patterns that are complex and difficult to diagnose. Isolated infarcts of the pons are uncommon and the neuro-ophthalmic presentation of pontine stroke can be quite variable. There is a paucity of cases in the literature documenting neuro-ophthalmic pathology as the sole or primary manifestation of pontine stroke. Here is presented the case of a unilateral internuclear ophthalmoplegia (INO) with concomitant skew deviation, contralesional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Initially, it was thought that this sign can be helpful to localize the lesion more rostral in the midbrain, where MLF connects with the subnucleus of 3rd nerve nucleus [4]. This concept is generally accepted by most clinicians [13]. However, further experiments and studies showed that this is unreliable due to inappropriate vergence signal carried by MLF [2,14].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was thought that this sign can be helpful to localize the lesion more rostral in the midbrain, where MLF connects with the subnucleus of 3rd nerve nucleus [4]. This concept is generally accepted by most clinicians [13]. However, further experiments and studies showed that this is unreliable due to inappropriate vergence signal carried by MLF [2,14].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that both conclusions indicated that the most important pathogenesis of strabismus was the modification of extracellular structure. It was quite easy to understand this conclusion demonstrating that the pathological study of strabismus demonstrated noticeable extracellular structure modification, including increased content of collagen fiber, and the gap between fibrous tissue, adipose tissue and muscle fiber widened ( 22 ). This phenomenon was also proved by a recent study in different study design.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in our patient, INO is explained by occurrence of strategically located lesion in the genu of facial colliculus close to the abducens nucleus causing interruption of normal horizontal eye conjugation. The presence of additional neurological signs such as skew deviation, contralesional exotropia and torsional nystagmus is seldom reported and transient [4]. These signs are possible associated with coexistent asymmetric tonus causing horizontal or vertical eye deviation and interruption of prenuclear vestibular input to the oculomotor nuclei causing nystagmus [4,5].…”
mentioning
confidence: 99%
“…The presence of additional neurological signs such as skew deviation, contralesional exotropia and torsional nystagmus is seldom reported and transient [4]. These signs are possible associated with coexistent asymmetric tonus causing horizontal or vertical eye deviation and interruption of prenuclear vestibular input to the oculomotor nuclei causing nystagmus [4,5].…”
mentioning
confidence: 99%